Gastroparesis syndromes: emerging drug targets and potential therapeutic opportunities. (4th March 2023) - Naing, Le Yu; Heckroth, Matthew; Mathur, Prateek; Abell, Thomas L
ABSTRACT: Introduction: Gastroparesis (Gp) and related disorders such as chronic unexplained nausea and vomiting and functional dyspepsia, known as gastropareis syndromes (GpS), have large unmet needs. Mainstays of GpS treatments are diet and drugs. Areas Covered: The purpose of this review is to explore potential new medications and other therapies for gastroparesis. Before discussing possible new drugs, the currently used drugs are discussed. These include dopamine receptor antagonists, 5-hydroxytryptamine receptor agonists and antagonists, neurokinin-1 receptor antagonists and other anti-emetics. The article also considers future drugs that may be used for Gp, based on currently known pathophysiology. Expert opinion: Gaps in knowledge about the pathophysiology of gastroparesis and related syndromes are critical to developing therapeutic agents that will be successful. Recent major developments in the gastroparesis arena are related to microscopic anatomy, cellular function, and pathophysiology. The major challenges moving forward will be to develop the genetic and biochemical correlates of these major developments in gastroparesis research.